Nucleation mechanism of multiple-order parameter ferroelectric domain wall motion in hafnia - Songsong Zhou; Andrew M. Rappe (Proceedings of the National Academy of Sciences, 2025)
Ferroelectric hafnia exhibits promising robust polarization and silicon compatibility for ferroelectric devices. Unfortunately, it suffers from difficult polarization switching. Methods to enable easier polarization switching are needed, and the underlying reason for this switching difficulty is not understood. Here, we investigated the 180 ° domain walls of hafnia and their motion through nucleation. We found that the domains of multiple-order parameter hafnia possess complicated three-dimensional dipole patterns and lead to domain walls of different symmetry. The most common domain wall type is a complex domain wall involving reversal of both polarization and tetragonality order parameters. This domain wall symmetry ensures a good matching of the dipoles perpendicular to the domain wall, which leads to low domain wall energy. However, this ensures a sharp, high-energy, charged domain wall on the edges of nuclei that results in difficult nucleation. Thus, this domain wall is too stable to move, which explains the switching difficulty of hafnia. By contrast, another simple domain wall, involving only polarization reversal, has a poor matching of dipoles perpendicular to the domain wall. This leads to higher domain wall energy and ensures a diffusive and low-energy charged domain wall that enables easier nucleation. This simple domain wall is thus not too stable and easier to move. Our theory advances domain wall nucleation theory from the field of conventional single-order parameter to multiple-order parameters. We propose controlling the populations of different domain wall types in hafnia as a way to enable fast polarization switching and lower coercive fields.